2015
DOI: 10.1038/srep11700
|View full text |Cite
|
Sign up to set email alerts
|

A novel recombinant lineage’s contribution to the outbreak of coxsackievirus A6-associated hand, foot and mouth disease in Shanghai, China, 2012-2013

Abstract: Since late 2012, coxsackievirus A6 (CVA6) has gradually become the predominant pathogen responsible for hand-foot-mouth disease (HFMD) in several provinces of China. A total of 626 patients diagnosed with HFMD in Shanghai, China from January 2012 to September 2013 were enrolled in this study. Of these, 292 CVA6 infected cases were subjected to clinical analyses. Whole-genome sequencing, recombination and phylogenetic analyses were also performed. A recombinant CVA6 monophyletic lineage was found during an outb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 36 publications
5
35
0
2
Order By: Relevance
“…In the analysis of the complete genome, CV‐A6 strains related to the HFMD outbreak in 2011 and 2013 were grouped in the same cluster as strains (GenBank accession number KM114057 and KP144345), which were also associated with HFMD. CV‐A6 strain isolated from the Chinese HFMD patient in 2013 (GenBank accession number KJ541155)was also classified in this cluster . CV‐A6 strains that caused the symptoms of HFMD overseas had been prevalent in Hyogo Prefecture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the analysis of the complete genome, CV‐A6 strains related to the HFMD outbreak in 2011 and 2013 were grouped in the same cluster as strains (GenBank accession number KM114057 and KP144345), which were also associated with HFMD. CV‐A6 strain isolated from the Chinese HFMD patient in 2013 (GenBank accession number KJ541155)was also classified in this cluster . CV‐A6 strains that caused the symptoms of HFMD overseas had been prevalent in Hyogo Prefecture.…”
Section: Discussionmentioning
confidence: 99%
“…CV-A6 strain isolated from the Chinese HFMD patient in 2013 (GenBank accession number KJ541155)was also classified in this cluster. 33 CV-A6 strains that caused the symptoms of HFMD overseas had been prevalent in Hyogo Prefecture. Although severely symptomatic HFMD was caused by CV-A6 in the United States in 2011-2012, 34 CV-A6 infection rarely leads to CNS disease.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the co-circulation of 6 virus lineages in 2014 is consistent with the hypothesis of multiple introductions of genetically distinct CV-A6 strains. In addition, a genetic analysis of complete CV-A6 genomes showed that strains collected during the 2012–2013 outbreak in Shanghai, China, were recombinant compared with strains collected before 2009 and were more frequently associated with generalized rash ( 29 ). …”
Section: Discussionmentioning
confidence: 99%
“…Some clinical observations showed that infection with the recombinant CV-A6 virus was associated with different clinical features from on generalized rash [28, 29]. However, there is limited report about the relationship between the recombination of CV-A2 and clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%